The Problem of Bending of Fibre Composite Viscoelastic Plates - Olejniczak, M. (Engineering Transactions, 1995)
A method is proposed for solving the problems of bending of prestressed fibrereinforced viscoelastic plates, subjected to durable loads. The plate considered is made of the primary material (the matrix, phase I), reinforced with densely spaced fibres (phase II) distributed in planes parallel to the middle plane of the plate. The compatibility condition of the two phases is introduced: ε = εI = εII, σ = σI + σII. A numerical algorithm has been prepared, the finite element method being applied. The problem is discretized with respect to time. The paper includes some examples of analysis and inferences.